The Effect of Analytic Text-Based Writing Strategies on ESL Argumentative Writing Among Malaysian Form-Six Students in Sabah, Malaysia: A Proposal - Rosalind Joannes; Asmaa AlSaqqaf (Fakultas Keguruan dan Ilmu Pendidikan Universitas Tanjungpura, 2022)
Producing effective and quality academic writing such as argumentative writing requires more than the regular writing ability, but rather analytical writing which would increase argumentation skills, and analytical thinking and promote higher cognitive skills. This study is conducted in response to a problem that exists within the Malaysian education setting where students have difficulties in presenting and expanding ideas of viewpoints convincingly, lack of knowledge of the subject matter, and insufficient linguistic competence. Therefore, this paper aims to investigate the effect of analytic text-based writing strategies on the students’ argumentative performance by proposing a conceptual framework that integrates the approach of text-based instruction and the writing model by Hyland (2003) that emphasizes the genre approach of teaching writing. This study will employ a mixed-method research approach and a quasi-experimental research design with a purposive sampling where two groups of Form-Six students will be involved in the study. The experimental group will be assigned to carry out a 12-week intervention program and the control group with regular classroom practices. Pre-test and post-test will be conducted on both groups before and after the intervention. These features of analytic text-based writing which largely focuses on reading and writing skills would be expected to bring a great improvement in the writing performance among Malaysian ESL learners in Sabah.